Clinical phenotypes and incidence of acute or recent hepatitis C virus infection and bacterial sexually transmitted infections among MSM with HIV - Juan Berenguer; Pablo Ryan; Luis Ramos-Ruperto; Luz Martín-Carbonero; Leire Pérez-Latorre; Ignacio De Los Santos; Adriana Pinto; María J. Vivancos; Eva Orviz; Beatriz Álvarez; José Sanz; Pilar Ruiz-Seco; et al. (AIDS, 2026)
Objective: Risk of acute/recent hepatitis C virus infection (ARHCV) and bacterial sexually transmitted infections (STIs) among MSM (MSM-HIV) is heterogeneous. We aimed to identify clinical phenotypes and assess their association with incident ARHCV and bacterial STIs. Design: A prospective multicenter cohort study. Methods: Between 2022 and 2024, MSM-HIV were recruited from 10 centers in Madrid and followed for 12 months with HCV and bacterial STI screening. App-based questionnaires captured behavioral and mental health data. Thirty-eight variables were analyzed using principal component analysis and hierarchical clustering to derive clinical phenotypes. Results: A total of 529 participants were included (median age 41 years). Three phenotypes were identified: CP1 ( n = 328, 62.0%), CP2 ( n = 133, 25.1%), and CP3 ( n = 68, 12.9%), representing different levels of sexual risk, substance use, and prior STI/HCV history. ARHCV incidence was 0.94, 0.72, and 11.76 per 100 person-years in CP1, CP2, and CP3, respectively, and was higher in CP3 than in CP1 (incidence rate ratio [IRR] 12.49, 95% confidence interval [CI] 3.00–73.08) and CP2 (16.25, 2.18–720.93). Bacterial STI incidence was 33.29, 60.83, and 61.76 per 100 person-years, respectively, and was higher in CP2 (IRR 1.83, 95% CI 1.36–2.46) and CP3 (IRR 1.86, 95% CI 1.27–2.68) than in CP1. Conclusion: Clinical phenotypes stratified ARHCV and bacterial STI incidence among MSM-HIV. ARHCV was concentrated in a small high-exposure subgroup, whereas bacterial STIs were more frequent in intermediate and high-exposure phenotypes. Phenotype-based approaches may help guide risk stratification and prevention in HIV care.